(untitled) (Texas Journal of Medical Science, 2023)
The biology department’s animal house at Iraq’s AL-Qadisiyah University hosted this study. It’s part of Iraq’s AL-Qadisiyah University, to demonstrate that the Kidney and Liver were subjected to oxidative stress from reactive oxygen species, which led to harmful consequences of the indomethacin medication on molecular level. 40 male Wister rats, aged (2 -3) months, weighing between 200 and 300 grams. Four groups of 10 rats. Control, 5 mg/kg, 7 mg/kg, and 10 mg/kg of indomethacin were given for 21 days to the groups. After the experiment, the animals were killed by hanging. After twenty-one days ,each of the study groups that received indomethacin therapy saw a statistically significant reduction (P <0.0 5), which was a decrease in the amount of the cyp27b1 gene, with the level of decrease being largest in the group that received treatment with ten milligrams per kilogram for 21 days. There was no difference (p>< 0.05) in the expression of the FGF2 gene between individuals in the untreated group and those who were given 5 mg, 7 milligrams, while 10 mg/kg of indomethacin showed significant increase. In conclusion indomethacin cause decrease in the level of cyp27b1gene, and cause increase expression in FGF2 gene